District Voter Turnout and Dyadic Representation in Congress. Issue 2 (4th May 2017) - Flavin, Patrick; Nelson, Julie
ABSTRACT: One of the most important tools by which citizens can influence their elected officials' behavior is through voting—the electoral connection. Previous studies demonstrate that the opinions of voters are better represented than the opinions of nonvoters within an electoral jurisdiction, but we do not know whether jurisdictions with higher levels of aggregate voter turnout are better represented by their elected officials compared to those with lower levels of turnout. Using data compiled across five congressional sessions (2003–2013), this article investigates whether congressional districts with higher voter turnout are better represented by their member of Congress (MC). We find evidence that district voter turnout positively conditions the relationship between district opinion and MC voting behavior even after accounting for the possible effects of electoral competition and district income and racial demographics. In addition, we uncover evidence that partisan differences exist in this conditioning effect such that higher voter turnout enhances roll call voting responsiveness among Democratic MCs but not among Republican MCs. These findings suggest that congressional districts as a whole benefit from a political responsiveness standpoint when more of their constituents turn out to vote and contribute to literatures on political representation, political participation, democratic accountability, and the U.S. Congress.